2020
DOI: 10.1007/s00213-020-05640-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nicotine and cannabis co-use during adolescence and young adulthood on white matter cerebral blood flow estimates

Abstract: Rationale Co-use of cannabis and nicotine is common among adolescents/young adults and is associated with poorer psychological and physical outcomes, compared with single substance use. Little is known about the impact of co-use on the developing brain. Objectives Preliminary investigation of the effects of nicotine on white matter (WM) cerebral blood flow (CBF) in adolescents/ young adults and its potential moderation by cannabis use. Methods Adolescent/young adult (16-22 years old) nicotine and tobacco produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 89 publications
1
16
0
Order By: Relevance
“…In one of our first papers focused on the co-use of nicotine and cannabis [ 14 ], our team found that higher levels of urinary cotinine (nicotine’s major metabolite, mean concentration = 89.3 ng/mL) significantly predicted decreased memory performance among both single substance users and co-users of cannabis and nicotine ages 16–22. In a follow-up paper examining differences in structural brain metrics with an overlapping yet larger sample of the same age, we found no evidence of poorer white matter tissue and blood flow integrity among co-users of nicotine and cannabis ( n = 53–55), although there was evidence of significantly poorer brain health outcomes among cannabis only users [ 15 , 16 ]. Others also failed to find poor structural brain integrity in young adult nicotine smokers [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 74%
“…In one of our first papers focused on the co-use of nicotine and cannabis [ 14 ], our team found that higher levels of urinary cotinine (nicotine’s major metabolite, mean concentration = 89.3 ng/mL) significantly predicted decreased memory performance among both single substance users and co-users of cannabis and nicotine ages 16–22. In a follow-up paper examining differences in structural brain metrics with an overlapping yet larger sample of the same age, we found no evidence of poorer white matter tissue and blood flow integrity among co-users of nicotine and cannabis ( n = 53–55), although there was evidence of significantly poorer brain health outcomes among cannabis only users [ 15 , 16 ]. Others also failed to find poor structural brain integrity in young adult nicotine smokers [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 74%
“…Globally, cannabis and tobacco (not to mention combining tobacco with alcohol) are commonly mixed together and smoked jointly (a practice called “mulling”). There is still limited knowledge about impact of co-use on metabolic changes and neural tissue development, but this has been associated already with adverse effects on educational outcomes, impaired emotional and physical functioning, lower cognitive performance and increased risk of substance-use disorders and addiction [ 57 ]. Moreover, studies show that combining stimulants has a particular effect on reducing GMV: There is a negative relation between the number of substances used (e.g., alcohol, cocaine, tobacco, cannabis) and the volume of the specific brain area—dorsal medial prefrontal cortex—and those alterations are related to the number of substances used, while ventrolateral prefrontal cortex pathology is specifically associated with tobacco use [ 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite these prevalence rates, few studies have examined the effects of cannabis and NTP use on neuroimaging outcomes [ 29 ]. The studies that have been completed by our laboratory show increased white matter tissue cerebral blood flow and poorer white matter integrity (i.e., decreased FA) among cannabis users without a history of nicotine use [ 30 ] and unique white matter profiles in nicotine and cannabis use groups; for example greater cannabis use was associated with greater FA in bilateral regions of the cingulum and the left fornix tracts, but only among those also reporting a history of nicotine [ 31 ]. These studies demonstrate that the interaction between cannabis and NTP use may lead to unique white matter morphometry in youth, and even introduce the possibility that NTP use may diminish or rescue the impact of cannabis use on the brain at an early age, prior to a long-term and chronic use history.…”
Section: Introductionmentioning
confidence: 99%